2013
DOI: 10.1021/ol401140d
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Arynes via Ate Complexes of Arylboronic Esters with an ortho-Leaving Group

Abstract: An efficient method of generating aryne has been achieved by treating ortho-(trifluoromethanesulfonyloxy)arylboronic acid pinacol ester with tert- or sec-butyllithium. Monitoring the reaction by (11)B NMR has indicated that a boron-ate complex formed in situ is the eventual precursor that converts into aryne near room temperature. The prior formation of the ate complex at a low temperature has enabled us to use various arynophiles, including those bearing base-sensitive groups. The ready availability of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…1 H-NMR yields were determined using 1,1,2,2-tetrachloroethane as an internal standard. The spectra obtained for products 3 [28], 5a [43], 5b-d [44], 5e [45], 5f [46], 5g [47], 7 [28], 9 [28], 11 [28], and 13 [48] were identical to those reported in the corresponding references.…”
Section: General Remarkssupporting
confidence: 75%
See 1 more Smart Citation
“…1 H-NMR yields were determined using 1,1,2,2-tetrachloroethane as an internal standard. The spectra obtained for products 3 [28], 5a [43], 5b-d [44], 5e [45], 5f [46], 5g [47], 7 [28], 9 [28], 11 [28], and 13 [48] were identical to those reported in the corresponding references.…”
Section: General Remarkssupporting
confidence: 75%
“…As a part of our studies focusing on highly strained alkynes, including arynes [24][25][26][27][28][29][30][31][32][33][34], we have been working on a project to develop new aryne generation methods. For example, we have recently succeeded in efficiently generating arynes from ortho-iodoaryl triflates bearing sensitive functional groups using a trimethylsilylmethyl Grignard reagent as an activator [30,31,33] instead of conventional activators such as n-butyllithium [35] or a turbo-Grignard reagent [36].…”
Section: Open Accessmentioning
confidence: 99%
“…We selected a benzotriazole (Bt) group as it can be easily introduced,14 is compatible with organolithium reagents,15 and is a good leaving group 16. However, we were also aware that boronate complexes possessing good leaving groups at the ortho ‐position were prone to undergo elimination leading to benzyne formation,17 which is a potentially competing process.…”
mentioning
confidence: 99%
“…Our group recently reported a new route using readily available ortho-borylaryl triflates C, from which arynes could be efficiently generated near room temperature via boron ate complexes, formed in situ by the treatment of boronic esters with tert-or sec-butyllithium. 6 This aryne generation method was mutually orthogonal to the popular method using orthosilylaryl triflates A, expanding the utility of aryne chemistry. Herein, we disclose another efficient way of generating aryne, being achieved by the rapid Grignard exchange reaction of ortho-sulfinylaryl triflates D.…”
mentioning
confidence: 99%
“…Considering that the reaction of 2-( p-tolylsulfinyl)iodobenzene with the phenyl Grignard reagent prefers iodomagnesium exchange to sulfoxidemagnesium exchange, 7 the sulfoxidemetal exchange reaction of 1a must be significantly enhanced by the electronwithdrawing effect of the triflyloxy group. Furthermore, the treatment of a mixture of three different types of aryne precursors 1a, ortho-silylphenyl triflate 20, 5f and ortho-borylphenyl triflate 21 6 with PhMgBr in the presence of 2,5-dimethylfuran (22) resulted in the selective consumption of 1a, leaving 20 and 21 intact ( Figure 3B). These results and our previous study 6 clearly showed that the rate of aryne generation significantly depends on the type of the anion equivalent group adjacent to the triflyloxy group and its activating conditions.…”
mentioning
confidence: 99%